Kinetic study of the dissolution of vanadyl sulfate and vanadium pentoxide in sulfuric acid aqueous solution. (18th May 2019) - El Hage, R.; Chauvet, F.; Biscans, B.; Cassayre, L.; Maurice, L.; Tzedakis, T.
Highlights: Vanadium (IV) sulfate VOSO4 and vanadium (V) pentoxide V2 O5 dissolution. Temporal evolution of the concentrations of VO 2+ and VO2 + at various temperatures. Understanding the dissolution limitations: V IV  → mass transfer; V V  → reaction with H + . Simple kinetic models to predict the evolution of VO 2+ and VO2 + concentrations. Abstract: The study deals with the 'vanadium (IV) sulfate' and 'vanadium (V) pentoxide' dissolution processes in 3 M H2 SO4 aqueous media. Several measurements of the concentration of dissolved VO 2+ and VO2 + were achieved in the range of 0–40 °C, and allowed to understand the limitations of the dissolution process ('endothermic' – mass transport for VOSO4 and 'exothermic' – reaction with the proton for V2 O5 ). In addition, simple models were proposed (diffusion/accumulation for VOSO4 and kinetic rate for V2 O5 ) and their resolution leads to theoretical kinetic equations describing the temporal evolution of these concentrations with satisfactory agreement with the experimental curves. Solubility's data and their temperature dependence were determined for both vanadium compounds involved.